ANALYSIS OF THE REQUIREMENTS FOR OPTICAL CABLES FOR CONSTRUCTION OF UNDERWATER TRANSMISSION SYSTEMS: ANALYSIS OF THE REQUIREMENTS FOR OPTICAL CABLES FOR CONSTRUCTION OF UNDERWATER TRANSMISSION SYSTEMS - Denev, Daniel; Tsankov, Tsvetoslav (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Analysis of the requirements for underwater transmission systems using optical fibers: The purpose of this article is to explain the fundamentals of the optical fibers for underwater placement. The specific requirements for the creation of underwater transmission systems are defined by the extreme environment. A general analysis of the current optic fiber has been conducted and their main characteristics are presented